Early clinical experience with the Carina robotic platform in urologic surgery - Hongkai Wang; Dalong Cao; Marcio Covas Moschovas; Junlong Wu; Beihe Wang; Kun Chang; Hui Wang; Yun Zhu; Bo Dai; Yao Zhu; Hailiang Zhang; Vipul R. Patel; et al. (BJUI Compass, 2025)
Abstract Objectives To evaluate the feasibility and safety of a new modular robotic surgical platform ‐ Carina Platform (Ronovo Surgical, Shanghai, China) in prostate and renal surgeries. Methods We performed 11 robot‐assisted radical prostatectomies (RARP) and 7 robot‐assisted partial nephrectomies (RAPN) using the novel Carina Platform at Fudan University Shanghai Cancer Center (Shanghai, China). The port placements, operating space setting, cart distances and patient positions for all surgeries were recommended according to the procedure cards developed by Ronovo Surgical. Outcomes include success rate (completion without conversion to laparoscopy or open surgery), docking time, total surgery time and safety evaluations such as estimated blood loss (EBL) and complications. Results The age of the patients ranged from 37 to 73 years, and the BMI ranged from 19.9 to 29.1 kg/m2. All operations were successfully completed without conversion to laparoscopy or extra port placement. For RARP, the mean docking time was 6.8 ± 5.6 min; the mean total surgery time was 156.3 ± 27.8 min; and mean EBL was 67.3 ± 39.2 ml. For RAPN, the mean docking time was 8.9 ± 1.6 min; the mean total surgery time was 146.0 ± 38.0 min; and mean EBL was 47.1 ± 7.6 ml. The mean warm ischemia time was 23.9 ± 6.7 min. There were no severe intraoperative or postoperative complications in 1‐month follow‐up. Conclusions This is the first clinical reporting outcomes of the Carina Platform in urologic procedures. The study provides evidence of feasibility and safety when performing RARP and RAPN with acceptable perioperative outcomes and minimal complications.